Phragmipedium warscewiczii, a new record for the Mexican orchid flora - Rodolfo Solano-Gómez; Eduardo Martínez-Ovando (Revista Mexicana de Biodiversidad)
Phragmipedium warscewiczii is reported as new record for the Mexican orchid flora from material recently collected in Chiapas. The species is described from Mexican specimens and it is compared with P. exstaminodium, its closest ally. The Mexican locality is the northernmost and most distant population for P. warscewiczii. Information on nomenclature, distribution, habitat, and factors of risk for this orchid is provided.